Tuberculosis: New Aspects of an Old Disease - Luisa Jordao; Otilia V. Vieira (International Journal of Cell Biology)
Tuberculosis is an ancient infectious disease that remains a threat for public health around the world. Although the etiological agent as well as tuberculosis pathogenesis is well known, the molecular mechanisms underlying the host defense to the bacilli remain elusive. In this paper we focus on the innate immunity of this disease reviewing well-established and consensual mechanisms like Mycobacterium tuberculosis interference with phagosome maturation, less consensual mechanism like nitric oxide production, and new mechanisms, such as mycobacteria translocation to the cytosol, autophagy, and apoptosis/necrosis proposed mainly during the last decade.